Imagery Training to Improve Lay-up Shoot Basketball at the Golden Ways Jombang Club - Saputro, Arnaz Anggoro (International Journal of Basketball Studies, 2023)
The purpose of this research is to develop imagery training to improve lay up shoot basketball at the Golden Ways Jombang basketball club. This development uses the Borg & Gall Research and Development (R&D) model using 9 steps. The product is validated by 3 experts, with: (1) psychologist, (2) basketball expert, and (3) media expert. The validator's assessment shows the results of media experts at 75% (quite valid), psychologists at 89.29% (very valid), basketball experts at 64.29% (quite valid). The media product was tested on a small group of 1 trainer and 4 athletes randomly selected based on ability. In large group trials, there were 1 coach and 14 athletes. The results obtained from the small test were 98% (very valid) and the large group test was 97% (very valid). Based on the results of the small and large group tests, the video product was declared fit for use.